Elevated HIF-1α levels in maintenance hemodialysis patients: a potential link to increased cognitive impairment risk - Guo, Lan; Jia, Caiyun; Luo, Ke; Liang, Juanrong; Wang, Lijun; Hui, Tianli (Frontiers in Aging Neuroscience, 2024)
IntroductionIn China, an increasing number of patients with end-stage renal disease are undergoing hemodialysis treatment. While this treatment yields relatively positive outcomes, the prevalence of cognitive impairment in patients receiving maintenance hemodialysis ranges from 24 to 80%, which is significantly higher than the general population.MethodIn this retrospective study, a total of 120 patients with kidney disease undergoing maintenance hemodialysis (MHD) were enrolled. The cognitive status of these patients was assessed using the C-MoCA score, which allowed categorization into two groups: the no cognitive impairment (NCI) group and the cognitive impairment (CI) group. Relevant clinical data, laboratory test results, as well as HIF-1α levels, were collected and analyzed to determine their relationship with the cognitive status of the patients.ResultsIn this study, a total of 45 patients (37.5%) developed CI, and their C-MoCA scores were significantly lower (21.6 ± 2.43) compared to patients in the NCI group (27.56 ± 1.48) (P < 0.001). The CI group was characterized by older age, lower levels of education, as well as lower levels of serum total bilirubin, serum total protein (TP), albumin, serum creatinine, and serum phosphorus in comparison to the NCI group. Additionally, CI patients exhibited higher levels of HIF-1α, received fewer monthly hemodiafiltration or hemoperfusion treatments, and had a lower rate of rosacastat treatment. Furthermore, univariate and multivariate logistic regression analyses demonstrated that older age (OR = 11.266 [95% CI: 2.775–45.747], P = 0.001) and higher HIF-1α (OR = 20.654 [4.831–88.298], P < 0.001) increased the risk of developing CI, while higher educational attainment reduced the risk of developing CI (> 12 years, OR = 0.004 [95% CI: 0.016–0.619], P≤0.001; 6–12 years, OR = 0.099 [95% CI: 0.000–0.049], P = 0.013).DiscussionCognitive impairment in patients undergoing maintenance hemodialysis (MHD) was found to be associated with older age, lower level of education, and higher HIF-1α levels. These factors should be taken into consideration by clinicians to monitor the cognitive status of MHD patients.